Hubungan Pengetahuan Ibu Hamil Tentang Gizi Dengan Kejadian Kekurangan Energi Kronik (KEK) di UPT Puskesmas Ulaweng - Susilawati Susilawati; Sumarni Sumarni; Sriwidyastuti Sriwidyastuti; Ermawati Ermawati (SENTRI: Jurnal Riset Ilmiah, 2025)
Maternal nutritional status plays an important role in the continuity and success of a pregnancy. The role of nutritional adequacy is very vital, starting from the first trimester of pregnancy until the first thousand days of life calculated from 270 days to 730 days of pregnancy, and the golden period when it influences the growth and development of children. Chronic energy deficiency (CED) in pregnant women is one of the nutritional problems that can impact the health of both the mother and the fetus. Pregnant women with CED are at risk of giving birth to Low Birth Weight (LBW) babies who have the potential to die, impaired growth and development of children. Lack of knowledge of pregnant women about nutrition affects maternal behavior, including in choosing foods to fulfill nutrition, thus causing a lack of nutritious food during pregnancy that can cause CED in pregnancy. The purpose of this study is to determine the relationship between pregnant women's knowledge about nutrition and the incidence of chronic energy deficiency. The research method used is quantitative with the Cross Sectional Study Survey method. The population in this study were all pregnant women in their first and second trimesters in the Ulaweng Community Health Center working area from January to May 2024, totaling 42 people with a sample size of 31 people determined using the Probability Sampling technique with Purposive sampling type. The instrument in this study used a questionnaire. The analysis used was the Chi-square test. The results showed that there was a relationship between pregnant women's knowledge about nutrition and the incidence of chronic energy deficiency, which was indicated by a p value = 0.001 <α = 0.05. The conclusion of this study is that the better the knowledge of pregnant women about pregnancy nutrition during pregnancy, the lighter the incidence of chronic energy deficiency (CED).